Regulation of ATRIP protein abundance by RAD9 in the DNA damage repair pathway - Peng, X-J; Liu, S-J; Bao, C-M; Liu, Y-Z; Xie, H-W; Cai, Y-H; Li, B-M; Hang, H-Y; Ding, X (Cellular and Molecular Biology, 2015)
Genotoxic stress activates checkpoint signaling pathways that activate the checkpoint kinases ATM and ATR, halt cell cycle progression, and promote DNA repair. A number of proteins act in concert with ATR to phosphorylate Chk1, including RAD17, the RAD9-RAD1-HUS1 complex, ATR/ATRIP and TopBp1. However, how these proteins involved act in concert with one another to propagate and maintain the checkpoint response is not well understood. Here, we reported that upregulation of RAD9 protein increased the quantity of ATRIP, suggesting that RAD9 activation will induce more efficient accumulation of ATRIP in vivo. Furthermore, the DNA damage-induced ATRIP foci formation was faster in the mRad9-/- ES cells. Also, ATRIP interacts specifically with RAD9, but not HUS1 and RAD1. Taken together, we suggested that RAD9 could affect both the ATRIP protein levels and DNA damage-induced ATRIP foci formation. Thus, we propose a role of RAD9 in the ATR-Chk1 pathway that is necessary for successful formation of the damage-sensing complex and DNA damage checkpoint signaling.